Characteristics of Entrepreneurship-Based Curriculum Objectives in the Second Elementary Education System of Iran - Nayeri, Amirreza; Mehdizadeh, Amirhossein; Kiyoumarsi , Firouz; Esmailzadeh , Zohreh; Sharifian , Leila (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective:  The objective of this study was to identify the characteristics of entrepreneurship-based curriculum objectives within Iran's second elementary education system.Methodology: The study employed a qualitative research design with an applied purpose. Data collection involved semi-structured interviews with 25 experts who had significant scientific or practical experience in entrepreneurship education. The sample was selected using purposive judgment sampling until theoretical saturation was achieved. The interviews were analyzed using Strauss and Corbin's open, axial, and selective coding processes to identify key themes and categories related to the research objective.Findings: The analysis revealed that the characteristics of entrepreneurship-based curriculum objectives in Iran’s second elementary education system fall into three main categories: (1) Strengthening and nurturing the entrepreneurial spirit in students, which includes knowledge and nature of entrepreneurship, development of entrepreneurial characteristics, and acquisition of economic literacy; (2) Raising student awareness about the self-employment process, encompassing opportunities for learning through action and experience, business law education, recognition of business creation opportunities, acquisition of financial skills, and marketing skills; (3) Fostering creative thinking in students, which covers critical thinking, creative thinking, teamwork, problem-solving, risk-taking, and responsibility.Conclusion: The findings underscore the importance of integrating entrepreneurship education into the elementary curriculum to foster essential entrepreneurial skills and attitudes from a young age.